Taxonomic study of leaf feeder lepidopteran larvae of rice pests and their parasitoids - Md Yusof, Nur Athiqah (2014)
Lepidopteran pests are considered as one of the important rice pests. Since many lepidopteran species intercept during larval stage, morphological identification of the pests at this stage is crucial. However, the taxonomic investigation of leaf feeder lepidopteran larvae is still lacking in Malaysia. Thus, this study was conducted to construct an illustrated key of leaf feeder lepidopteran larvae of rice pests, to study the taxonomy and life cycle of the outbreak species Mythimna venalba (Moore) and identification of larval lepidopteran parasitoids by using Polymerase Chain Reaction (PCR) based approach. Nine species of leaf feeder lepidopteran larvae from four families (Nymphalidae, Hesperiidae, Pyralidae and Noctuidae) were identified. Eight of them were identified to species, whilst one larva was identified to genus. The species identified were: Melanitis leda, Parnara guttata, Pelopidas mathias, Cnaphalocrocis medinalis, Marasmia patnalis, Spodoptera mauritia, Spodoptera sp., Mythimna venalba and Mythimna loreyi. An illustrated key to those species was constructed. The outbreak species in Kedah in 2011 was identified as Mythimna venalba based on adult male genitalia identification. This was confirmed with molecular identification with the similarity hit of 97.2% in BOLD system. Result showed that M. venalba underwent six instars, which was determined by the width of size head capsule. The mean of head width were 0.33 ± 0.00 mm, 0.46 ± 0.01 mm, 0.74 ± 0.01 mm, 1.16 ± 0.03 mm, 1.97 ± 0.04 mm and 2.70 ± 0.02 mm respectively. The development of the larvae fits Dyar‟s rule as it follows the regular geometrical progression. The life cycle of M. venalba completes in 35 days. The chaetotaxy of the larva confirmed that it belonged to the family Noctuidae because the positions of setae L1 and L2 that lie prespiracular in prothorax, where L2 is ventrad from L1, and further grouped, belonging to the subfamily Hadeninae with the presence of one and three SV setae on each A1 and A2 segments respectively. The variable positions and distances of L2 and SD1 setae could provide information at species level. There were 13 parasitoids were identified from two orders, Hymenoptera and Diptera. Phylogenetic analysis by constructing Neighbour-Joining tree showed that every individual parasitoid was clustered together to their respective order, family and genus. Eleven of species were identified to genus level, whilst one was identified to subfamily. The parasitoids obtained were Cotesia ruficrus, Apanteles sp., Bracon sp., Dolichogenidea sp., Megaselia sp. Sarcophaga sp. and subfamily Bethylinae. The results of DNA sequence analysis by NCBI and BOLD showed that the similarity percentage for all parasitoids that ranged from 89 to 100%.